2013
DOI: 10.11621/pir.2013.0403
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and tolerance for uncertainty predict the engagement of emotional intelligence in personal decision making

Abstract: The current study investigated the relationships among creativity, tolerance for uncertainty (TU), and emotional intelligence (EI) in a selected sample of undergraduate students (n=145). We found differential patterns of intercorrelations among these constructs in students majoring in psychology, music, and stage directing, and we also established group differences in these constructs in the three groups of students. Thus, the use of emotional information in personal decision making in different subsamples is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…La IE influye, por tanto, en la capacidad para utilizar estrategias de afrontamiento adaptativas ante las emociones negativas o para afrontar situaciones estresantes, siendo un factor determinante para la salud mental y física (Martins et al, 2010). Asimismo, Pavlova y Kornilova (2013) mostraron que cuanto más desarrollada era la inteligencia emocional de la persona, mayor era su tolerancia a la incertidumbre. Por su parte, Barberis et al (2019) encontraron que la inteligencia emocional media entre la incertidumbre y la ansiedad y depresión.…”
Section: Factores Psicoambientales Y Cognitivos De Los Estados Emocio...unclassified
See 1 more Smart Citation
“…La IE influye, por tanto, en la capacidad para utilizar estrategias de afrontamiento adaptativas ante las emociones negativas o para afrontar situaciones estresantes, siendo un factor determinante para la salud mental y física (Martins et al, 2010). Asimismo, Pavlova y Kornilova (2013) mostraron que cuanto más desarrollada era la inteligencia emocional de la persona, mayor era su tolerancia a la incertidumbre. Por su parte, Barberis et al (2019) encontraron que la inteligencia emocional media entre la incertidumbre y la ansiedad y depresión.…”
Section: Factores Psicoambientales Y Cognitivos De Los Estados Emocio...unclassified
“…Thus, EI influences the ability to use adaptive coping strategies when addressing negative emotions or facing stressful situations, being a determining factor for mental and physical health (Martins et al, 2010). Furthermore, Pavlova and Kornilova (2013) showed that the more developed an individual’s emotional intelligence, the greater their tolerance for uncertainty. Barberis et al (2019) found that emotional intelligence mediates between uncertainty and anxiety, and depression.…”
mentioning
confidence: 99%
“…человек определился в выборе); осмысленность выбора при этом связана и с реализацией опоры на свои интеллектуальные возможности. Считается, что выбор человека всегда осознан, хотя от него могут оставаться скрытыми как смысловые, так и другие регуляторы направленности субъективных предпочтений [7].…”
unclassified